CuTe chains on Cu(111) by deposition of one-third of a monolayer of Te: Atomic and electronic structure - Kißlinger, Tilman; Raabgrund, Andreas; Geldiyev, Begmuhammet; Ammon, Maximilian Michael; Rieger, Janek; Hauner, Jonas; Hammer, Lutz; Fauster, Thomas; Schneider, M. Alexander (Physical Review B, 2020)
The surface atomic and electronic structure after deposition of one-third of a monolayer Te on Cu(111) was determined using a combination of low-energy electron diffraction (LEED), scanning tunneling microscopy and spectroscopy (STM/STS), angle-resolved single and two-photon photoelectron spectroscopy (ARPES /AR-2PPE), and density functional theory (DFT) calculations. Contrary to the current state in literature, Te does not create a two-dimensional surface alloy but forms Cu2Te2 adsorbate chains in a (2√3×√3)R30∘ superstructure. We establish this by a high-precision LEED-IV structural analysis with Pendry R factor of R=0.099 and corroborating DFT and STM results. The electronic structure of the surface phase is dominated by an anisotropic downward dispersing state at the Fermi energy EF and a more isotropic upward dispersing unoccupied state at E−EF=+1.43eV . Both states coexist with bulk states of the projected band structure, and are therefore surface resonance

Epitaxial Cobalt Oxide Films with Wurtzite Structure on Au(111) - Ammon, Maximilian Michael; Baumann, Sara; Kißlinger, Tilman; Rieger, Janek; Fauster, Thomas; Redinger, Josef; Hammer, Lutz; Schneider, M. Alexander (Physica Status Solidi-Rapid Research Letters, 2021)
Several-nanometer-thick, closed, and epitaxial cobalt(II) oxide films with wurtzite crystal structure (w-CoO) are grown on Au(111) and their structural and electronic properties analyzed. The structural quality of the (Formula presented.) oriented, oxygen-terminated, and unreconstructed films allow the application of surface-science methods to unravel the properties of this unusual polymorph of CoO and may pave the way for future thin-film applications. An experimental structural analysis by low-energy electron diffraction (LEED-IV) is presented with an excellent agreement between measured and calculated intensity spectra expressed by a Pendry R-factor of (Formula presented.) and few-picometer error bounds in the parameter values. Using scanning tunneling spectroscopy (STS) the bandgap of the semiconducting films is found to be 1.4 ± 0.2 eV. Ultraviolet photoelectron spectroscopy (UPS) confirms the presence of a gap and the position of the Fermi level (E F). The structural results of density functional theory calculations using (hybrid) functionals to treat electron correlations and van der Waals forces agree well with the experimentally determined structure of the antiferromagnetic w-CoO films. In contrast to generalized gradient approximation (GGA)+U calculations, the Heyd–Scuseria–Ernzerhof hybrid functional reproduces the semiconducting nature correctly and predicts surface states in the gap which might pin E F in agreement with STS and UPS.
Created from Fastlane, Scopus look-up
Keywords: bandgaps; cobalt oxide; electronic properties; polymorphism; structural analyses

Epitaxial inorganic metal-halide perovskite films with controlled surface terminations - Rieger, Janek; Kißlinger, Tilman; Raabgrund, Andreas; Hauner, Jonas; Niesner, Daniel; Schneider, M. Alexander; Fauster, Thomas (Physical Review Materials, 2023)
Metal-halide perovskite (MHP) thin films for next-generation solar cells are typically fabricated by wet-chemical synthesis in which surface properties such as the orientation of surface facets and their termination cannot be controlled. MHP device efficiencies depend critically on those surface properties. We demonstrate the epitaxial growth of several nanometer thick purely (001)-orientated films of CsPbBr3 and CsSnBr 3 MHPs on Au(001) by molecular beam epitaxy. The epitaxial films are in a cubic phase aligned with the substrate. Their surfaces are singly terminated and can be modified for the first time. While the CsBr and PbBr2 surface terminations differ in terms of their atomic structure and defect content, the films are intrinsic semiconductors irrespective of the termination. The work function of the PbBr2-terminated surface is increased by 0.7eV, which has drastic implications for the level alignment at MHP interface

Orbital-Driven Rashba Effect in a Binary Honeycomb Monolayer AgTe - Unzelmann, Maximilian; Bentmann, Hendrik; Eck, Philipp; Kißlinger, Tilman; Geldiyev, Begmuhammet; Rieger, Janek; Moser, Simon; Vidal, Raphael C.; Kissner, Katharina; Hammer, Lutz; Schneider, M. Alexander; Fauster, Thomas; et al. (Physical Review Letters, 2020)
The Rashba effect is fundamental to the physics of two-dimensional electron systems and underlies a variety of spintronic phenomena. It has been proposed that the formation of Rashba-type spin splittings originates microscopically from the existence of orbital angular momentum (OAM) in the Bloch wave functions. Here, we present detailed experimental evidence for this OAM-based origin of the Rashba effect by angle-resolved photoemission (ARPES) and two-photon photoemission experiments for a monolayer AgTe on Ag(111). Using quantitative low-energy electron diffraction analysis, we determine the structural parameters and the stacking of the honeycomb overlayer with picometer precision. Based on an orbitalsymmetry analysis in ARPES and supported by first-principles calculations, we unequivocally relate the presence and absence of Rashba-type spin splittings in different bands of AgTe to the existence of OAM.
CRIS-Team WoS Importer:2020-05-15

Roadmap on organic-inorganic hybrid perovskite semiconductors and devices - Schmidt-Mende, Lukas; Dyakonov, Vladimir; Olthof, Selina; Ünlü, Feray; Lê, Khan Moritz Trong; Mathur, Sanjay; Karabanov, Andrei D.; Lupascu, Doru C.; Herz, Laura M.; Hinderhofer, Alexander; Schreiber, Frank; Chernikov, Alexey; et al. (APL Materials, 2021)
Metal halide perovskites are the first solution processed semiconductors that can compete in their functionality with conventional semiconductors, such as silicon. Over the past several years, perovskite semiconductors have reported breakthroughs in various optoelectronic devices, such as solar cells, photodetectors, light emitting and memory devices, and so on. Until now, perovskite semiconductors face challenges regarding their stability, reproducibility, and toxicity. In this Roadmap, we combine the expertise of chemistry, physics, and device engineering from leading experts in the perovskite research community to focus on the fundamental material properties, the fabrication methods, characterization and photophysical properties, perovskite devices, and current challenges in this field. We develop a comprehensive overview of the current state-of-the-art and offer readers an informed perspective of where this field is heading and what challenges we have to overcome to get to successful commercialization.
CRIS-Team Scopus Importer:2021-11-19

Surface carrier dynamics and diffusion in inorganic metal-halide perovskite films - Rieger, Janek; Hauner, Jonas; Niesner, Daniel; Fauster, Thomas (Physical Review B, 2023)
Carrier dynamics in metal-halide perovskites, in particular diffusion, has typically been investigated on micrometre-length scales and above. However, surfaces and interfaces modify the carrier dynamics, e.g., by interface band bending and recombination. To investigate the carrier dynamics and diffusion at the surface, we use time-resolved photoelectron spectroscopy which is sensitive to the photoexcited carriers in the topmost few nm of the material. We extract electron mobilities in well-ordered CsPbBr 3 (001) and CsSnBr3(001) films at room temperature of 31±6 and 13±1cm2V−1s−1, respectively. The mobility in CsPbBr3(001) increases to 200±8cm2V−1s−1 at 90 K, indicating strong electron-phonon coupling for electrons at the conduction band minimum. Temperature-dependent photoemission experiments find different phonon coupling mechanisms for high-energetic electrons and holes at the valence band maximum and in the main valence band